DIAGNOSTIC ACCURACY OF CONTRAST ENHANCED CT FOR DETECTION OF RENAL CELL CARCINOMA TAKING HISTOPATHOLOGY AS GOLD STANDARD - Akram, Faiza; Arfa Mazhar; Hamza Javed; Muhmmad Fayyaz; Ayub Khan; Khalil Ahmad (Journal of Ayub Medical College Abbottabad, 2023)
Background: Renal cell carcinoma being the commonest primary renal malignancy of adulthood accounts for approximately 80-90% renal malignant lesions. The purpose of radiological imaging modalities when devising the treatment options for renal masses is crucial as it significantly influence the clinical outcome and prognosis of the disease. Subjective impression by a radiologist for diagnosing a mass lesion is known to be critical and its precision is improved by contrast enhanced CT as demonstrated by certain retrospective analyses. We aimed to ascertain the diagnostic accuracy of contrast enhanced computed tomography to diagnose renal cell cancers by verifying through histopathology reported diagnoses. Methods: This Cross-sectional (validation) study was carried out in Radiology and Urology departments of Ayub Teaching Hospital; Abbottabad, from 1st November 2020 to 30th April 2022. The study population included all admitted symptomatic patients with age range 18-70 years of either gender. The patients were subjected to detailed clinical examination and history and an ultrasound and contrast enhanced CT abdomen and pelvis. CT scans were reported under supervision of single consultant radiologist. Data was analyzed in SPSS version 20.0. Result: Mean age of the patients was 38.88±11.62 years ranging from 18 to 70 years and mean duration of symptoms was 54.64±49.171 ranging from 3 to 180 days. All of the total 113 patients underwent contrast enhanced CT scan and later operated to confirm the diagnoses by histopathology. The comparison yielded true positive (TP) cases to be 67, True Negative (TN) 16, False Positive (FP) 26, and 04 False Negative (FN) as per CT scan diagnoses. CT scan had a diagnostic Accuracy of 73.45% with 94.37% sensitivity and 38.10% specificity. Conclusion: Contrast-enhanced CT has a high sensitivity for making the diagnosis of renal cell carcinoma; however, its specificity is low. A multidisciplinary approach is necessary to overcome the low specificity. Therefore, collaboration between radiologists and urologic oncologists should be considered while devising treatment plan for patients.